Analysis of the Impact of Workshop-Based Teacher Training Programs on the Development of Teacher Competencies - Yoana Dian Pramestuti (Dinasti Review Publisher, 2026)
This study examines the impact of workshop-based training programs on the development of teacher competencies in Surabaya. Grounded in the concept of Human Resource Management in education, this research addresses the gap between expected teacher competencies and actual conditions, as indicated by national competency test results. A descriptive qualitative approach with a case study method was employed, using observation and documentation to collect data from various workshop programs conducted between 2024 and 2026. The findings reveal that workshop-based training has significantly contributed to improving teachers’ competencies across pedagogical, professional, social, and personal dimensions. The programs emphasize key areas such as digital learning, Artificial Intelligence (AI), STEAM, numeracy, and character education, reflecting the demands of 21st-century education. In addition, collaborative partnerships among government institutions, universities, schools, and the creative industry enhance the relevance and effectiveness of these programs. Furthermore, the results indicate that workshops promote experiential learning, enabling teachers to develop practical skills, critical thinking, and adaptive mindsets. Teachers are increasingly transitioning from knowledge transmitters to facilitators and content creators. Workshop-based training proves to be an effective strategy for fostering sustainable professional development and improving the quality of education.